1999
DOI: 10.1161/01.atv.19.9.2154
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Photodynamic Therapy and γ-Irradiation on Vascular Smooth Muscle Cells and Matrix

Abstract: Abstract-␥-Irradiation (␥-RT) and photodynamic therapy (PDT) are known to inhibit intimal hyperplasia. The common mechanism is that both modalities produce free radicals, but unlike ␥-RT, PDT generates them through the absorption of light by photosensitizers. The purpose of this in vitro study was to assess the differences that PDT and ␥-RT have on the fibroproliferative response after vascular injury by comparing their effects on vascular smooth muscle cells (SMCs) and on the extracellular matrix (ECM). Mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…It has been shown that γ-irradiation of cultured VSM cells in vitro inhibits proliferation of these cells after stimulation (45). Three months after transplantation, irradiated grafts showed severe TA, similar to nonirradiated grafts, suggesting recipient origin of neointimal cells.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that γ-irradiation of cultured VSM cells in vitro inhibits proliferation of these cells after stimulation (45). Three months after transplantation, irradiated grafts showed severe TA, similar to nonirradiated grafts, suggesting recipient origin of neointimal cells.…”
Section: Discussionmentioning
confidence: 97%
“…This method is based on the ability of viable cells to reduce MTT to form colored formazan product (Heckenkamp et al 1999). Briefly, cells were cultured in 96-well plates at a density of 1× 10 4 cells per well in media with different pH-pH 7.3, pH 6.8, pH 6.3, and pH 5.8.…”
Section: Cellular Proliferation Assaymentioning
confidence: 99%
“…12 The mechanism by which PDT induces this cytotoxicity in vivo remained to be elucidated. There is in vitro evidence that PDT can cause apoptosis in vascular smooth muscle cells 18. but only one study so far provided evidence for apoptosis in the microvasculature in vivo.…”
Section: Discussionmentioning
confidence: 99%